Upaya Meningkatkan Kompetensi Pedagogik Guru Dalam Memanajemen Kelas Melalui Supervisi Akademik Di Sekolah Dasar Binaan Kota Lhokseumawe Tahun 2021 - Munira, Munira (Journal of Technology and Literacy in Education, 2022)
This study aims to determine the increase in teacher pedagogical competence in managing classes through the application of academic supervision in elementary schools under the guidance of Lhokseumawe City in 2021. This research was carried out at elementary schools assisted by researchers in Lhokseumawe City in odd semesters in 2021. The research was carried out approximately for 4 months, starting from July to October 2021. The research subjects were teachers assisted by researchers who were at SD Negeri 10 Banda Sakti, SD Negeri 17 Banda Sakti, SD Negeri 22 Banda Sakti, SD Negeri 6 Muara Dua, SD Negeri 3 Blang Mangat, SD Negeri 7 Blang Mangat, SD Negeri 8 Blang Mangat, and SD Negeri 10 Blang Mangat, totaling 16 teachers. The research conducted was School Action Research (PTS) which was conducted in two cycles. Each cycle consists of planning stage, implementation stage, observation stage and reflection stage. Research data collection techniques obtained from the results of observations. The data analysis technique used in this study is descriptive qualitative using a percentage formula. The results of the study showed that in the first cycle, the teacher's ability to manage classes in the implementation of learning still had deficiencies. The overall average value obtained is 76.97%. Then as many as 11 teachers still got sufficient criteria and only 5 people got good criteria. Meanwhile, in cycle II, the teacher's ability to manage classes in the implementation of learning has increased. The overall average value obtained is 89.35%. Experienced an increase of 12.38% from cycle I. Then as many as 5 teachers got very good criteria and 11 teachers got good criteria. So it can be concluded that through the application of academic supervision it can improve teacher pedagogic competence in managing classes at Lhokseumawe City-targeted Elementary Schools in 2021.